Physiological parameterization of thyroid radioiodine kinetics. Issue 7 (July 2018) - Eterović, Davor; Brdar, Dubravka; Barić, Ana; Sladić, Sanda; Omrčen, Tomislav; Punda, Ante
Abstract : Background: In radioiodine thyroid dosimetry, the serial uptake measurements are variously analyzed, but an underlying model, derived from plausible assumptions, is lacking. Methods: We derived that, upon oral administration, the intrathyroid iodine activity is the sum of two monoexponential functions, defined by iodine activity given, its volume of distribution, and thyroid and whole-body clearances, as well as the decay constants of the particular isotope. Applications: The individual parameters of the model function are fitted to the patient's uptake data, allowing direct calculation of the cumulated thyroid activity and assessment of thyroid parameters which, unlike thyroid uptake, are not confounded by renal function. The approximate method, based on Marinelli's formula, underestimates the 131 I thyroid absorbed dose from 1 to 8%, the more the faster thyroid iodine elimination. Conclusion: The derived parametric function of radioiodine intrathyroid kinetics facilitates the dosimetry, providing the reference standard to assess the simpler, more approximate methods; is applicable to any iodine radioisotope; and set-ups the method for assessment of thyroid and whole-body iodine clearances.